Rapid degradation of atrazine by hydroxyl radical induced from montmorillonite templated subnano-sized zero-valent copper. (August 2017) - Hong, Ran; Guo, Zupei; Gao, Juan; Gu, Cheng
Abstract: In this study, subnano-sized zero-valent copper (ZVC) was synthesized using montmorillonite clay mineral as the template. The discrete distribution of surface charge on montmorillonite effectively separates the formed ZVC particles and inhibits their aggregation. X-ray diffraction result indicates that the size of ZVC particles on montmorillonite is ∼6 Å, which is much smaller than nano-ZVC prepared by conventional method. The montmorillonite templated ZVC (ZVCMMT) shows superior reactivity as indicated by the degradation of atrazine, over 90% atrazine (15 μM) could be degraded in a few min. Hydroxyl radical is confirmed as the reactive species, which is produced from the activation of oxygen by ZVC. It was also shown that the degradation process is strongly dependent on the hydration status of synthesized ZVCMMT. The freeze dried ZVCMMT exhibits higher reactivity compared to freshly prepared ZVCMMT, which can be explained by the higher adsorption of atrazine and oxygen residue on freeze dried ZVCMMT surface. In addition, the toxicity of atrazine is significantly decreased after the reaction with ZVCMMT, indicating that ZVCMMT could be used as a promising material for rapid remediation of persistent organic contaminants. Graphical abstract: Highlights: Sub-nano sized Cu 0 was synthesized in the confined space of montmorillonite clay. Molecular oxygen can be activated by clay-templated Cu 0 to form hydroxyl radical. Clay-templated Cu 0 shows superior reactivity to degrade atrazine.